Analisis Kesulitan Mahasiswa Program Studi Statistika Angkatan 2024 Universitas Negeri Medan Dalam Mengerjakan Tugas Mini Riset - Aisyah Novianti; Elisabeth Putri Dayanti; Emily Theresia Silaen; Nia Rizkita Tambunan; Sudianto Manullang; Putri Maulidina Fadilah (Journal of Innovative and Creativity, 2025)
Students of the Statistics Study Program often face difficulties in completing mini research projects, which are an essential part of project-based learning. This study aims to analyze the difficulties experienced by Statistics students at Universitas Negeri Medan (UNIMED), specifically the 2024 cohort, in conducting their mini research assignments. A descriptive quantitative approach was used. Data were collected through questionnaires and interviews, with 69 students selected using a simple random sampling technique. The questionnaire instrument was tested for validity and reliability. The results showed that all items were valid, and the reliability coefficient of 0.753 indicated that the instrument was consistent and reliable. The analysis revealed that students primarily struggled with understanding statistical concepts, processing data using statistical software, and writing structured research reports. These findings highlight the need for additional guidance in both methodological and technical aspects of mini research. This study is expected to serve as an evaluation reference for lecturers and study programs to improve the quality of research-based learning in higher education. Keywords: Learning Difficulties, Mini Research, Statistics Students, Validity, Reliability.